2004
DOI: 10.1046/j.1529-8817.2004.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA and Y‐Chromosome Variation in the Caucasus

Abstract: SummaryWe have analyzed mtDNA HVI sequences and Y chromosome haplogroups based on 11 binary markers in 371 individuals, from 11 populations in the Caucasus and the neighbouring countries of Turkey and Iran. Y chromosome haplogroup diversity in the Caucasus was almost as high as in Central Asia and the Near East, and significantly higher than in Europe. More than 27% of the variance in Y-haplogroups can be attributed to differences between populations, whereas mtDNA showed much lower heterogeneity between popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
128
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(136 citation statements)
references
References 38 publications
6
128
0
2
Order By: Relevance
“…The clustering of groups on the basis of geographic rather than linguistic relationships is in keeping with previous studies of genetic diversity among Caucasian populations. 10,11 However, the complete mtDNA genome sequences do reveal some additional genetic similarity between the two Turkic-speaking groups (Azeri and Turks) that was not evident in previous studies. Presumably, the sharing of some Central Asian mtDNA haplogroups by Azeri and Turks (Table 3) accounts for this signal of genetic similarity between the Azeri and the Turks.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The clustering of groups on the basis of geographic rather than linguistic relationships is in keeping with previous studies of genetic diversity among Caucasian populations. 10,11 However, the complete mtDNA genome sequences do reveal some additional genetic similarity between the two Turkic-speaking groups (Azeri and Turks) that was not evident in previous studies. Presumably, the sharing of some Central Asian mtDNA haplogroups by Azeri and Turks (Table 3) accounts for this signal of genetic similarity between the Azeri and the Turks.…”
Section: Discussionmentioning
confidence: 70%
“…[6][7][8][9][10][11][12][13][14][15] These studies were mostly based on sequences of the first hypervariable segment of the noncoding mtDNA control region (HV1) and Y chromosome binary marker variation in various groups from this region. mtDNA studies reveal a high level of diversity, exceeding that within all of Europe and only slightly lower than West Asian mtDNA diversity, which might indicate an old age of human populations from this region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32][33][34][35][36] Limited pedigree data suggest very high mean inbreeding coefficients (0.005-0.0134), 32,37 whereas population genetic studies have been restricted to autosomal Alu insertion and STR markers, the Y chromosome and mtDNA. 32,[37][38][39][40][41][42][43][44][45] …”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Others suggest that the genetic legacy of the Caucasus region is mainly because of the people who crossed or invaded this territory in historic times. 12 A large amount of genetic data on the Caucasian populations, based on classical markers, 9,[13][14][15] Alu insertion polymorphisms, 10 mitochondrial DNA 10,16 and the non-recombining portion of the Y chromosome (NRY) 17 have shown that neither geography nor linguistics have had a strong influence on the genetic structure of these ethnic groups and that genetic drift appears to be the main factor acting in the region. Furthermore, Y chromosomes of highland Dagestan ethnic groups appear to have undergone genetic drift independently of the population history of mitochondrial and autosomal loci, suggesting that social rules, and not simply geographic isolation, are the causal agents for the high NRY diversity observed among highlanders.…”
Section: Introductionmentioning
confidence: 99%